2023
DOI: 10.20944/preprints202303.0177.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Precision Information Data Acquisition Method for Mobile Equipment Based on Fractional Partial Differential Equations

Abstract: The information data accuracy affects the working reliability of production management system directly. Mobile equipment is an important part of integrated manufacturing system, in the course of its works, due to the complex working environment and the dynamic change of its position, it lead to the important problem of information detection distortion. Because the application of fractional differential operator has the dual functions of enhancing signal strength and reducing data error, we puts forward a data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To solve these problems, our team has engaged in research on methods using fractional-order calculus theory in data processing for many years and found that the fractional-order differential operator has the dual function of improving the signal strength and reducing the variability between information data. Therefore, it can effectively improve the transmission distance and detection accuracy of information [25][26][27][28][29][30][31]. Based on previous research, in this study, we applied fractional calculus theory to the detection of underground space information data.…”
mentioning
confidence: 99%
“…To solve these problems, our team has engaged in research on methods using fractional-order calculus theory in data processing for many years and found that the fractional-order differential operator has the dual function of improving the signal strength and reducing the variability between information data. Therefore, it can effectively improve the transmission distance and detection accuracy of information [25][26][27][28][29][30][31]. Based on previous research, in this study, we applied fractional calculus theory to the detection of underground space information data.…”
mentioning
confidence: 99%